Menciptakan Ikatan Harmonis Antara Orang Tua Dan Anak Dalam Perspektif Al-Qur’an - Ana Rahmawati; Novi Fitriyanti; Laili Novita Sari (CV. ITTC INDONESIA, 2024)
As a basis human life, the Qur'an has improved all aspects of life, including the relationship between parents and children. However, many children do not care or pay lees attantions to thair parentsparents when their parents arel elderly. In this study, researches used the interpretations of Al maraghi and Al azhar to see the attitudes, actions and relationship between children and parents in Al Isra verses 23-24. In relation to the interpretations of the Q.S Luqman 14, ath tabari and Ibnu katshir agree that allah SWT commands us to do good to our parents. Including the Qur'an, Al Isra latter verses 23-24, the interpretations of Al maraghi and Al Azhar and serveal other literatures. The results show that: children's views and actions towards parents both parties agree that a child should receive care and meet all the medsos of their parents when they are adulst.